THE QUALITATIVE EVALUATION OF IRANIAN 1st GRADE HIGH SCHOOL ENGLISH TEXTBOOK - Maryam Adelifar, Masumeh Arjmandi (International Journal of Research Science and Management, 2014)
This study investigates around the content analysis of a English high school textbook and obeys descriptive analysis to find out different aspects of textbook, which serves as the material for students. This qualitative research circles around a library research that investigates the appearance of the textbook, titles and texts embedded in lessons, vocabulary items, grammar and syntax focus, pronunciation, function of language and cultural and also social aspects. Finally, researcher found out that the content of the textbook is not practical to the students’ needs, which generally should elevate their language competency and off course, their performance in real situation as observed in class situation. Therefore, the hypothesis of the study proved considering the discussion provided in latest section.